ANALISIS IMPLEMENTASI SAK EMKM PADA USAHA MIKRO KECIL DAN MENENGAH: STUDI KASUS UMKM KARS PRODUCTION - Ramadhan, Rizal; Ma’sumah, Siti; Dwi Setyasih, Riztina (Economics, Social, and Humanities Journal (Esochum), 2024)
Research conducted on MSMEs Kars Production aims to design and present financial statements based on SAK EMKM. This research considers theories and information relevant to the accounting cycle. The purpose of this study is to increase understanding and knowledge and produce good, accurate, and adequate financial statements. With quality financial statements, Kars Production MSMEs can develop their business well and control their operational activities effectively. In addition, the information contained in the financial statements can also be used as a basis for decision-making for the development of the business they are doing. The type of research conducted is qualitative research. This research is a descriptive research action that is more concerned with using analysis with an inductive approach. The approach used is a type of qualitative descriptive research approach that consists of collecting data to answer various questions about the final status of the research subject. The results of this study show a discrepancy between the process of recording, preparing, and reporting finances at Kars Production MSMEs with the applicable financial report-making standards, namely SAK EMKM. This is because the MSMEs in their reports are still made only in accordance with the knowledge they have, which is still very simple. Of course, this will make it difficult for MSMEs in the right decision-making process to develop their business in the future.